Defining the Contribution of AMP-activated Protein Kinase (AMPK) and Protein Kinase C (PKC) in Regulation of Glucose Uptake by Metformin in Skeletal Muscle Cells - Turban, Sophie (American Society for Biochemistry and Molecular Biology, 2012)
The importance of AMP-activated protein kinase (AMPK) and protein kinase C (PKC) as effectors of metformin (Met) action on glucose uptake (GU) in skeletal muscle cells was investigated. GU in L6 myotubes was stimulated 2-fold following 16 h of Met treatment and acutely enhanced by insulin in an additive fashion. Insulin-stimulated GU was sensitive to PI3K inhibition, whereas that induced by Met was not. Met and its related biguanide, phenformin, stimulated AMPK activation/phosphorylation to a level comparable with that induced by the AMPK activator, 5-amino-1-β-d-ribofuranosyl-imidazole-4-carboxamide (AICAR). However, the increase in GU elicited by AICAR was significantly lower than that induced by either biguanide. Expression of a constitutively active AMPK mimicked the effects of AICAR on GU, whereas a dominant interfering AMPK or shRNA silencing of AMPK prevented AICAR-stimulated GU and Met-induced AMPK signaling but only repressed biguanide-stimulated GU by ∼20%. Consistent with this, analysis of GU in muscle cells from α1(−/−)/α2(−/−) AMPK-deficient mice revealed a significant retention of Met-stimulated GU, being reduced by ∼35% compared with that of wild type cells. Atypical PKCs (aPKCs) have been implicated in Met-stimulated GU, and in line with this, Met and phenformin induced activation/phosphorylation of aPKC in L6 myotubes. However, although cellular depletion of aPKC (>90%) led to loss in biguanide-induced aPKC phosphorylation, it had no effect on Met-stimulated GU, whereas inhibitors targeting novel/conventional PKCs caused a significant reduction in biguanide-induced GU. Our findings indicate that although Met activates AMPK, a significant component of Met-stimulated GU in muscle cells is mediated via an AMPK-independent mechanism that involves novel/conventional PKCs.